Eco-consciousness, dwelling and anxiety in selected works of John Burnside - Aldhafeeri, Hilalah Dughayyim S. (2017)
This thesis studied children exploitation, rape, and paranoia from an interdisciplinary perspective, namely, ecocriticism and psychoanalysis.The concepts of ecoconsciousness and dwelling were applied to analyze the selected works’ environmental places, such as gardens, forests, landscapes and so forth. On the other hand, psychoanalysis was specified to Freud’s concept of anxiety to analyze the protagonists’ anxious feelings caused by children exploitation, rape, and paranoia.By utilizing these concepts, the study unraveled the selected works’ natural settings as being therapeutic exits for the protagonists’ anxiety. Thus, the selected works’ the protagonists in the selected works are studied as seeking solace and peace of mind in nature. Therefore, the dissertation aimed to examine nature and anxiety in John Burnside’s novels The Dumb House (1997), The Locust Room (2001), and A Summer of Drowning (2011). The study achieved three objectives. The first objective examined the selected works protagonists’ anxiety as a result of children exploitation, rape, and paranoia. The second objective discovered the role of natural settings for the protagonists’ anxious feelings. Ultimately, the third objective identified the connection between natural settings and anxiety in the selected works. The conceptual interdisciplinarity was limited to ecocriticism and psychoanalysis. The main focus was on two ecocritical concepts; dwelling and eco-consciousness. First, the concept of dwelling was mainly cited by using Greg Garrard’s concept of dwelling and its use to analyze the natural settings of fictional works. Dwelling, therefore, was applied to analyze the selected works’ settings since they are abound with natural scenes, such as forests, landscapes, gardens and so forth. Second, the analysis drew upon Cheryll Glotfelty’s concept of eco-consciousness and its critical interface with the concept of dwelling. Both concepts are the ecocritical side of the research. On the other hand, psychoanalysis was limited to Sigmund Freud’s concept of anxiety. The concept of anxiety was used to explore the protagonists’ anxious inner feelings in the selected works.The protagonists share a common trait of anxiety, and consequently, they become psychologically anxious and begin seeking refuge for psychic comfort in nature. This is because they suffer from their involvement in children exploitation, rape, and paranoia, in Burnside’s The Dumb House (1997), The Locust Room (2001), and A Summer of Drowning (2011), respectively. As a result, they go sauntering in natural places, like forest paths, gardens, and meadows and meet some animals where they feel psychically calm. Hence, the selected works’ natural settings were analyzed as remedial exits for the protagonists’ anxiety. Thus, the significance of this study was its analysis of the anxious protagonists who seek peace and solace of mind in nature. In the light of these findings, the study provided three recommendations for further research. First, the selected works could be studied by applying ecocriticism but from an ecological perspective.For example, the killing of certain animals, such as locusts and rabbits, in The Locust Room, may lead to their extinction. Therefore, the selected works might be interpreted as a response to probable imminent ecological apocalypse. Second, the study of paranoia and anxiety could be elaborated by using feminism theory. In A Summer of Drowning, the protagonist Liv would be studied in terms of feminist insights. She becomes paranoid of men whom she thinks are responsible of destroying her mother. In this sense, the novel could be studied as a critique of androcentric hegemony. Third, the technical structure of the selected works would be identified by applying formalism. The narrative omniscient narrator might be a subject for formalistic analysis. As in The Dumb House, the novel’s depiction of precise natural settings might be explored as the author’s own interest in nature where he finds tranquility and psychic comfort. Thus, the selected works could also be studied by applying children psychoanalysis to explore major themes in relation to anxiety and paranoia.